ENVIRONMENTAL LUCK AND THE STRUCTURE OF UNDERSTANDING. (March 2020) - Boyd, Kenneth
ABSTRACT: Conventional wisdom holds that there is no lucky knowledge: if it is a matter of luck, in some relevant sense, that one's belief that p is true, then one does not know that p. Here I will argue that there is similarly no lucky understanding, at least in the case of one type of luck, namely environmental luck. This argument has three parts. First, we need to determine how we evaluate whether one has understanding, which requires determining what I will call understanding's evaluative object. I argue that as the evaluative object of (at least a traditional conception of) knowledge is a belief in a proposition, the evaluative object of understanding is a mental representation of a relational structure. Next, I show that arguments that environmental luck is incompatible with understanding miss the mark by considering cases in which one has a belief in a proposition is lucky to be true, instead of ones in which one's mental representation of a relational structure is lucky to obtain. I agree, then, with those who argue that one can have understanding when one's beliefs are environmentally lucky to be true, but that this compatibility is not relevant when considering the question of whether one can have environmentally lucky understanding. I then present what I take to be a properly constructed case which shows the incompatibility of environmental luck with understanding.